Metal-Organic Framework-101 (MIL-101): Synthesis, Kinetics, Thermodynamics, and Equilibrium Isotherms of Remazol Deep Black RGB Adsorption - Vo Thi Thanh Chau; Huynh Thi MinhThanh; Pham Dinh Du; Tran Thanh Tam Toan; Tran Ngoc Tuyen; Tran Xuan Mau; Dinh Quang Khieu (Journal of Chemistry)
In the present paper, the synthesis of metal-organic framework-101 (MIL-101) and Remazol Deep Black RGB (RDB) adsorption on MIL-101 were demonstrated. The kinetics of RDB adsorption on MIL-101 was studied using Weber’s intraparticle diffusion model and the pseudo-first- and pseudo-second-order kinetic models. Particularly, the statistical method of piecewise linear regression and multi-nonlinear regression was employed to analyse the adsorption data according to the previously mentioned kinetic models. The results indicated that the adsorption process followed the three-step pseudo-first-order kinetic equation, which was consistent with the results of the intraparticle diffusion model with three linear segments. This model best described the experimental data. In addition, the adsorption isotherm data were studied using five adsorption models, namely, Langmuir, Freundlich, Redlich–Peterson, Toth, and Sips in nonlinear forms, and the Langmuir model is the most appropriate for the experimental data. The values of energies of activation of adsorption were calculated, and they revealed that the adsorption process was of endothermic chemical nature. A statistical comparison using Akaike information criterion to estimate the goodness of fit of the kinetic and isotherm models was presented.